2013
DOI: 10.3109/00952990.2013.799175
|View full text |Cite
|
Sign up to set email alerts
|

Therapist predictors of treatment delivery fidelity in a community-based trial of 12-step facilitation

Abstract: Background and aims Therapist characteristics may be associated with variation in consistency, quality and effectiveness of treatment delivery. We examined associations between treatment fidelity and therapist education, experience, treatment orientation, and perceived skills in a randomized, multi-site trial of Twelve Step Facilitation (TSF). Methods Raters scored audio-recorded, TSF sessions (n = 966; 97% of TSF sessions) from 32 community-based, trained therapists for adherence, competence, empathy, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…Although the relationship between years of education and the overall quality score was no longer significant when scores were averaged across clients for each clinician, the magnitude of the correlation was virtually the same across the smaller and larger samples. The significant positive relationship between clinician years of education and fidelity ratings is consistent with some previous research in this area (Campbell et al, ). The relational factor involves competence‐related elements that require more responsiveness and skill on the part of the clinician while the technical factor required adherence‐related behaviour that is more explicitly prescribed in the treatment manual (Rollinson et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Although the relationship between years of education and the overall quality score was no longer significant when scores were averaged across clients for each clinician, the magnitude of the correlation was virtually the same across the smaller and larger samples. The significant positive relationship between clinician years of education and fidelity ratings is consistent with some previous research in this area (Campbell et al, ). The relational factor involves competence‐related elements that require more responsiveness and skill on the part of the clinician while the technical factor required adherence‐related behaviour that is more explicitly prescribed in the treatment manual (Rollinson et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…The availability of comprehensive fidelity ratings for the entire TSF sample provided an opportunity to study relationships of fidelity with other variables, including predictors and outcomes. A prior report (Campbell, Buti, et al, 2013) found that therapists reporting self-efficacy in basic counseling skills had higher adherence, competence, and empathy delivering the TSF intervention and those with graduate degrees had higher adherence. In contrast, therapists with more positive attitudes towards 12-Step groups and self-efficacy in addiction-specific counseling skills had lower adherence ratings.…”
Section: Treatment Retention and Outcomes In Tsfmentioning
confidence: 93%
“…In an ancillary study, we assessed the reliability and concurrent validity of the Twelve Step Facilitation Adherence Competence Empathy Scales (TSF ACES), a ratings measure of treatment delivery fidelity based on an expansion of the adherence rating scales used in STAGE-12 (Campbell, Manuel et al, 2013). Trained, independent raters evaluated fidelity of all audio-recorded TSF sessions.…”
Section: Treatment Retention and Outcomes In Tsfmentioning
confidence: 99%
“…The measurement of treatment fidelity would benefit from the inclusion of a treatment manual, therapist certification, fidelity ratings of treatment, supervision [42], adherence scales, competence scales and structured professional development opportunities. This comprehensive tool kit would support the facilitation and delivery of programs locally, regionally and internationally.…”
Section: Recommendationsmentioning
confidence: 99%